O problema da formação (bildung) em Sobre o futuro dos nossos estabelecimentos de ensino, de Nietzsche - Rodrigues, Eduardo José Lobo [UNESP] (2015)
It is investigating the conferences, spoken by F. Nietzsche, entitled On the future of our Educations Institutions the problem of formation (Bildung) that is discussed by Nietzsche as a criticism of the German educational model. Such criticism seeks to highlight that educational institutions do not promote the formation of an authentic culture to young people, both in the system and the junior college, but a preparation for professional activities and the market system. The educational model of the German state tends to promote the extension and maximum magnification of culture, and the tendency to reduce, to the weakening of the culture itself. Nietzsche thus draws a distinction between professional institutions, these institutions for the necessities of life, and cultural institutions. The definition of culture proposed by Nietzsche departs from modern dogmas and principles, taking the idea of true and instinctive understanding of nature, the Greek model and the German neo-humanism.